Effects of rogue ryanodine receptors on Ca2+ sparks in cardiac myocytes. Issue 2 (21st February 2018) - Chen, Xudong; Feng, Yundi; Huo, Yunlong; Tan, Wenchang
Abstract : Ca 2+ sparks and Ca 2+ quarks, arising from clustered and rogue ryanodine receptors (RyRs), are significant Ca 2+ release events from the junctional sarcoplasmic reticulum (JSR). Based on the anomalous subdiffusion of Ca 2+ in the cytoplasm, a mathematical model was developed to investigate the effects of rogue RyRs on Ca 2+ sparks in cardiac myocytes. Ca 2+ quarks and sparks from the stochastic opening of rogue and clustered RyRs are numerically reproduced and agree with experimental measurements. It is found that the stochastic opening Ca 2+ release units (CRUs) of clustered RyRs are regulated by free Ca 2+ concentration in the JSR lumen (i.e. [Ca 2+ ]lumen ). The frequency of spontaneous Ca 2+ sparks is remarkably increased by the rogue RyRs opening at high [Ca 2+ ]lumen, but not at low [Ca 2+ ]lumen . Hence, the opening of rogue RyRs contributes to the formation of Ca 2+ sparks at high [Ca 2+ ]lumen . The interplay of Ca 2+ sparks and Ca 2+ quarks has been discussed in detail. This work is of significance to provide insight into understanding Ca 2+ release mechanisms in cardiac myocytes.